2017
DOI: 10.1038/nchem.2741
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of phosphine ligands demonstrates enhancement of nickel catalysis via remote steric effects

Abstract: The field of Ni-catalysed cross-coupling has seen rapid recent growth because of the low cost of Ni, its earth abundance, and its ability to promote unique cross-coupling reactions. Whereas advances in the related field of Pd-catalysed cross-coupling have been driven by ligand design, the development of ligands specifically for Ni has received minimal attention. Here, we disclose a class of phosphines that enable the Ni-catalysed Csp3 Suzuki coupling of acetals with boronic acids to generate benzylic ethers, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
196
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(206 citation statements)
references
References 35 publications
5
196
0
5
Order By: Relevance
“…2023 To date, it remains a significant challenge to quantitatively describe the catalyst-substrate dispersion interaction and distinguish it from other types of non-covalent interactions, such as steric and electrostatic effects. 2426 Inspired by the distortion/interaction model established by Houk and Bickelhaupt, 27 herein we report a ligand-substrate interaction model for the analysis of ligand effects on the through-space and through-bond interactions between the catalyst and the substrate. Based on energy decomposition analysis 28,29 of computed transition states, this model allows for the quantitative prediction of the effects of ligand-substrate dispersion interactions on catalyst’s activity.…”
Section: Introductionmentioning
confidence: 99%
“…2023 To date, it remains a significant challenge to quantitatively describe the catalyst-substrate dispersion interaction and distinguish it from other types of non-covalent interactions, such as steric and electrostatic effects. 2426 Inspired by the distortion/interaction model established by Houk and Bickelhaupt, 27 herein we report a ligand-substrate interaction model for the analysis of ligand effects on the through-space and through-bond interactions between the catalyst and the substrate. Based on energy decomposition analysis 28,29 of computed transition states, this model allows for the quantitative prediction of the effects of ligand-substrate dispersion interactions on catalyst’s activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from one of our groups 23 and others 24 have identified numerous multi-dimensional correlations between molecular parameters and reaction outcomes. The computationally derived parameters in this study only revealed relatively complex models to describe the rate measurement, the simplest of which involved four unique terms.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the P-Ni-P angle did not lead to acorrelation on the selectivity and yields,thus reinforcing the validity of the gem-dialkyl effect. [19] As depicted in Figure 3, av ariety of electronically unbiased Grignard reagents were accommodated. Finally,inascreening for additives,CsF was found to aid in preventing further isomerization.…”
Section: Angewandte Chemiementioning
confidence: 99%